ANALYZING LANGUAGE REGISTERS IN MOBILE LEGENDS: BANG-BANG FOR EDUCATIONAL INSIGHTS - Mujazin, M; Buono, Shanti Pitaloka (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Register is a phenomenon where the use of language variations or terms that have peculiarities based on the situation and language needs and this phenomenon contains types and functions in speech. This research aims to find out the types and functions of utterances used in the game Mobile Legends: Bang-Bang. The data of this research comes from the terms in the Mobile Legends game. This research is a descriptive qualitative research that aims to describe a research object with a description. The researcher uses observation and documentation methods to collect data. The researcher used the theory of register types from Martin Joos (1962) and Halliday's register language function (1985). The researcher found four types of registers namely casual, formal, consultative and intimate registers with a total of 60 data divided into 40 casual registers (70%), 3 formal registers (5%), 14 consultative registers (23.33%), and 1 intimate register (1.67%) and the researcher found five functions of register language namely function of information, Regulatory, interactional, instrumental, and function of personal with a total of 60 data divided into 38 data of function of information (63.33), 15 data of regulatory function (25%), 3 data of interactional function (5%), 3 data of instrumental function (5%), and 1 data of personal function (1.67). The most used register type is casual register (70%) and the most used function is function of information (63,33%). the study identified the potential educational benefits of leveraging the gaming environment for language learning. Integrating Mobile Legends' language registers into educational practices can enhance students' linguistic skills and foster a more interactive and immersive learning experience.